Prologo. - Carreño, Antonio (Las Novelas de Unamuno, 1988)
Presents the book "Las Novelas de Unamuno," written by Rosenda Díaz-Peterson, with a prologue by Antonio Carreño and published by Scripta Humanistica in 1987. It discusses the philosophy and literary works of Spanish writer Miguel de Unamuno including his novels "Paz en la Guerra," "Abel Sánchez" and "San Manuel Bueno, mártir."